Identifying behavioural factors influencing waste sorting at source in developing countries: a case study of the RANAS approach to recover organic waste for agriculture in Bukavu - Mathis, M. (Swiss Federal Institute of Technology Zurich, 2022)
Waste is present in large quantities in cites of the Global South. To reduce the amount of waste ending up in public spaces and the environment, the largest fraction of the waste, organic waste, should be recovered and transformed to compost to be reused in agriculture. Composting is still struggling to be successful through dealing with badly sorted organic material. This increases cost for compost production and prohibits this technology to be largely applied. Previous research found that the problem of bad sorted waste is mainly due to the lack of sorting behaviour adoption at source. From psychology we know that behaviour is driven by psychological factors. Finding psychological factors and identifying which of these factors are influencing the behaviour is the first step to change the behaviour as based on these factors targeted interventions can be developed. In Bukavu, Democratic Republic of Congo getting pure organic matter from households is very difficult up to date. Waste is posing many environmental and sanitary problems within the city. Changing the behaviour of waste sorting in this city might be a promising solution to improve the recovery of organic waste for agricultural use in the case of Bukavu. In this study I researched demographic, contextual, and psychological behaviour factors existing and influencing waste sorting in Bukavu, by using RANAS approach coming from Theory of Planned behaviour. From the psychological factors, I identified in interviews with 22 households and 8 key informants working with these households, perceived risks connected to waste, negative and positive feelings to waste sorting, benefits from waste sorting, group norms influencing waste sorting, and self-regulation factors driving waste sorting in Bukavu. These factors were all mentioned by the interviewees through sub-items for each of these factors. With the most expressed items from the interview, and items from psychological theory I designed a survey to measure how strong the items of the behaviour factors are expressed in 146 households. Further, I measured the organic waste sorting precision from the households. Through a regression analysis I identified the psychological self-regulation factor, and the contextual factor availability of a durable waste bin to influence waste sorting precision significantly. Further, in a separate ANOVA analysis I identified significant differences between collectors working with the different households. The conducted analysis showed important factors influencing waste sorting in Bukavu. The identified influential factors should be further addressed in interventions to achieve behaviour change in waste sorting in Bukavu. Through appropriate behaviour change techniques, interventions can be implemented and evaluated. This will show if the observed factors are causal for improving waste sorting precision, and if through this change, improvement of recovery of organic waste in Bukavu can be achieved. If this is successful, behaviour change in waste sorting should be applied in other cities of the Global South to see if it works there as well.